Interconnected Histories: Searching for Jacob Gens’ Grave and Instead Finding a Forgotten Early 18th Century Cemetery - Philip Reeder; Harry Jol; Alastair McClymont; Paul Bauman; Mantas Daubaras (Histories, 2025)
Jacob Gens, the head of the Vilnius Ghetto Police Force, and eventually the entire Ghetto during the Holocaust, was murdered on 14 September 1943 by the head of the Vilnius Gestapo. Historical documents and Holocaust survivor testimonies indicate that he was killed at a site that became known as the Rasu Street Prison, and not the Gestapo Headquarters, as it is widely believed. In 2016, research was completed at the Rasu Street Prison site using ground penetrating radar (GPR) and electrical resistivity tomography (ERT) to locate subsurface reflection patterns that possibly indicate the location of where Jacob Gens is buried. Intersecting GPR and ERT reflection patterns were discovered and a plan was put in place to excavate that location. The excavation revealed the presence of human remains at 1.45 m below the surface. A skull and upper torso were exposed, and two teeth were collected for DNA and radiocarbon analysis. The DNA from the tooth was compared to Jacob Gens’ daughter’s DNA, and this comparison yielded a negative result, so the human remains were not those of Jacob Gens. The radiocarbon analysis provided a date between 1685 and 1735. In 1705, a plot of land was donated to the Visitation Monastery, which used this plot, and which coincides with the location of the Rasu Street Prison, as a cemetery for the poor. In 1709 and 1710, a plague epidemic was prevalent in Vilnius, as was turmoil and famine associated with the Great Northern War (1700 to 1721). Based on these discoveries, rather than finding the remains of Jacob Gens, it is likely that we found human remains that are part of a forgotten 18th century cemetery associated with the Visitation Monastery.